The influence of workload, work-life balance, and role conflict on the performance of employee students (DLC) at Stikubank University Semarang - Leony Anggita Maharani; Suhana Suhana (Universitas Nusa Cendana, 2026)
This study examines the influence of workload, work–life balance, and role conflict on the performance of student employees at Stikubank University. In the context of increasing academic and occupational demands, student employees often face challenges related to balancing educational responsibilities and work commitments, which may affect their overall performance. Employing a quantitative research design, data were collected through structured questionnaires distributed to 100 respondents selected using purposive sampling techniques. The data were analysed using IBM SPSS Statistics. The findings reveal that workload and work–life balance exert positive and significant influences on employee performance, with work–life balance emerging as the most dominant factor in enhancing the performance of student employees. These results indicate that effective management of time, personal well-being, and work responsibilities contributes substantially to maintaining productivity and performance among working students. In contrast, role conflict was found to have no significant effect on performance, suggesting that student employees were generally capable of managing their dual roles without substantial disruption to their work outcomes. The study highlights the strategic importance of balancing academic and occupational responsibilities and contributes to the broader literature on student employment, work–life balance, and human resource management in higher education contexts. Keywords: Workload; Work-Life Balance; Role Conflict; Performance